1975
DOI: 10.1029/ja080i019p02854
|View full text |Cite
|
Sign up to set email alerts
|

diurnal variation of the sodium dayglow

Abstract: We present here an explanation of the erroneous interpretations of spectrosco. pic sodium dayglow measurements which led to a large diurnal variation. In fact, the diurnal variation is proved to be either small or nonexistent. This result is confirmed by balloon-borne experimental measurements of the sodium twilight and dayglow intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In Figure 7 we present the ratio of the average December-January abundance to the average June-July abundance for a number of stations. Table I gives , 1961] originally suggested a considerable enhancement of sodium abundance during the day, but it now appears that the interpretation of these measurements was in error [Chanin and Goutall, 1975]. Both the absorption and the dayglow measurements reported by Burnett et al [1972,1975] show no diurnal variation.…”
Section: Seasonal Variationmentioning
confidence: 95%
“…In Figure 7 we present the ratio of the average December-January abundance to the average June-July abundance for a number of stations. Table I gives , 1961] originally suggested a considerable enhancement of sodium abundance during the day, but it now appears that the interpretation of these measurements was in error [Chanin and Goutall, 1975]. Both the absorption and the dayglow measurements reported by Burnett et al [1972,1975] show no diurnal variation.…”
Section: Seasonal Variationmentioning
confidence: 95%
“…Measurements taken over small solid angles exhibit significant fluctuations in time scales of 10 min [Burnett et al, 1975]. Some observations with Zeeman photometers [Blamont and Donahue, 1964;Albano et al, 1970;Gadsden et al, 1966] have shown a midday maximum of abundance; however, these results have been shown to be in error by Chanin and Goutail [1975]. No such maximum was seen in the Pepsios data of Burnett et al [1975], who observed the dayglow rather than the solar absorption reported here.…”
Section: Introductionmentioning
confidence: 48%
“…It became evident that a very much larger number of measurements than previously attempted would be necessary to deduce reliable diurnal variation trends from the absorption res'ults. The very large discrepancy between the direct absorption and the original Zeeman photometer results has been removed by improved interpretation of the Zeeman photometer data [Chanin and Goutail, 1975]; however, limits on the magnitude of any remaining diurnal variation need still to be obtained. An extended series of observations carried out at the University of Wisconsin in Madison (43ø4.5'N, 89ø24.3'W) and aimed at determining the daytime abundance of atmospheric sodium by the direct absorption of sunlight [Partowmah, 1975] is the subject of this report.…”
mentioning
confidence: 64%
“…Recently, Chanin and Goutail [ 1975] have critically analyzed the sodium dayglow data obtained by means of the Zeeman photometer and concluded that the large diurnal sodium abundance variation that had been deduced from such measurements was an artifact resulting partly from the filling in of Fraunhofer lines (Ring effect) and partly from the increasing reflected light flux through the sodium layer as the sun illuminates the surface of the earth more directly, thereby increasing the total resonance scattering. Their conclusion was that the abundance enhancement admitted by their data could be no more than a factor of 1.5 and that in most cases the absence of Chanin and Goutall [1975] in that diurnal variations as large as previously supposed [Gadsden et al, 1966] are not found; however, the suggestion that there may be no enhancement appears to be inconsistent with our data.…”
Section: Discussionmentioning
confidence: 99%